Pocketbook voting, social preferences, and expressive motives in referenda - Johannes Meya; Panu Poutvaara; Robert Schwager (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2017)
We develop and test a theory of voting and turnout decisions that integrates self-interest, social preferences, and expressive motives. Our model implies that if pocketbook benefits are relevant, voters either perceive their impact on the outcome to be non-negligible, or expressive motivations do not play a role in the decision on how to vote. Conversely, if own pocketbook benefits do not explain voting, then voting is expressive. If the perceived probability of being pivotal is non-negligible, social preferences and expressive concerns are observationally equivalent. Our empirical analysis studies collective choices which are analogous to decisions on local public goods. We consider referenda among university students on whether to collectively purchase deeply discounted flat rate tickets for public transportation and cultural amenities. Individual usage data allow quantifying the monetary benefits associated with each ticket. As voters had precise information on the individual costs and benefits, our setting comprises a real-world laboratory of direct democracy. We find that monetary benefits strongly influence participation and voting. However, social or expressive motives, such as stated altruism, environmental concerns, and paternalism, are decisive for a significant minority. Our results rule out purely expressive voting and imply that a substantial share of the electorate perceived their impact on the outcome to be non-negligible.
urn:nbn:de:bvb:19-epub-38425-6
Keywords: D72; H41; D64; 330; pocketbook voting; social preferences; expressive voting; instrumental voting; public goods; altruism; referendum